From Replacement Migrations to the “Great Replacement”: Demographic Reproduction and National Populism in Europe - Domingo, Andreu (Advances in Social Sciences Research Journal, 2020)
This article aims to analyse how the distorted story about demographic evolution—demographic reproduction and its relationship with social stratification—is becoming substantial enough to erode democracy. In order to demonstrate this, it first analyses the origin of the “Great Replacement” metaphor that is used to refer to international migration, inside and outside the discipline of demography, as part of an allegory referring to demographic transformations in the twenty-first century, together with the metaphors “demographic winter” (referring to population ageing), and “demographic suicide” (when speaking of declining fertility). Second, it relates these three metaphors with right-wing national populist movements and explains how they have developed as conspiracy theories.